Cooked : a natural history of transformation - Pollan, Michael (New York : The Penguin Press, 2013)
Pollan explores the previously uncharted territory of his own kitchen. Here, he discovers the enduring power of the four classical elements--fire, water, air, and earth--to transform the stuff of nature into delicious things to eat and drink.
Includes bibliographical references (pages [447]-458) and index.
Keywords: Cooking; Cooks